The White Clover Single-Copy Nuclear Gene TrNAC002 Promotes Growth and Confers Drought Resistance in Plants Through Flavonoid Synthesis - Youzhi Zhang; Wei Fu; Qi Pu; Zhirui He; Zhou Li; Lin Liu; Xiao Ma; Yan Peng (Plants)
White clover (Trifolium repens) is vulnerable to drought stress. In response to abiotic stress, plants are regulated by NAC transcription factors. The NAC in white clover has not been thoroughly documented until recently. We have identified one white clover NAC transcription factor called TrNAC002. TrNAC002’s coding sequence is localized to specific regions on the 3P and 5O chromosomes of white clover and is part of a single-copy nuclear gene. Subcellular localization demonstrates that TrNAC002 is located in the nucleus, while the transcriptional activity assay indicates its transcriptional activity. Arabidopsis plants overexpressing TrNAC002 (OE) exhibit enlarged leaves and increased lateral root growth compared to the wild type (WT). Additionally, the expression levels of the shoot apical meristem (SAM), WUSCHEL (WUS), DNA-binding protein (DBP), and auxin-induced in root cultures3 (AIR3) genes are significantly higher in OE as compared to WT. These findings imply that TrNAC002 could promote vegetative growth by increasing the expression of these genes. Under natural drought stress, OE can survive in dry soil for a longer period of time than WT. Furthermore, OE exhibits a lower level of reactive oxygen species (ROS) level and a higher content of flavonoids than WT. This is also positively correlated with an increased flavonoid content. In white clover, the expression of TrNAC002, chalcone synthase (CHS), and chalcone isomerase (CHI) in leaves demonstrates significant upregulation after drought stress and ABA treatment, as does the flavonoid content. However, the pTRV-VIGS experiment suggests that pTRV2-TrNAC002 white clover shrinks compared to the Mock and Water controls. Additionally, pTRV2-TrNAC002 white clover displays a statistically higher malondialdehyde (MDA) content than the Mock and Water controls, and a significantly lower level of total antioxidant activities, flavonoid content, CHS and CHI relative expression than that of the Mock and Water controls. These findings indicate that TrNAC002 responds to drought and modulates flavonoid biosynthesis in white clover. This study is the first to suggest that TrNAC002 likely responds to drought via ABA and enhances plant drought resistance by synthesizing flavonoids.